2017
DOI: 10.3847/1538-4357/aa7bed
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of the Massive Star-forming Galaxies with an Outside-in Assembly Mode

Abstract: Previous findings show that massive (M * > 10 10 M ⊙ ) star-forming (SF) galaxies usually have an "inside-out" stellar mass assembly mode. In this paper, we have for the first time selected a sample of 77 massive SF galaxies with an "outside-in" assembly mode (called "targeted sample") from the Mapping Nearby Galaxies at the Apache Point Observatory (MaNGA) survey. For comparison, two control samples are constructed from MaNGA sample matched in stellar mass: a sample of 154 normal SF galaxies and a sample of 6… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 102 publications
(161 reference statements)
3
26
1
Order By: Relevance
“…Furthermore, the metallicity difference can be as large as 0.2 dex, which is roughly equal to what we find here. The dominated mechanism of this finding is still under debate (Ellison et al 2008;Yabe et al 2012;Sánchez Almeida et al 2014;Wang et al 2017;Sánchez Almeida & Dalla Vecchia 2018), which is likely a combined effect of metal-poor gas accretion, metalrich gas outflow, and the metal-enrichment from current star formation activities. However, the metallicity difference between cSFGs and eSFGs vanishes at stellar mass greater than 10 10.5 M ⊙ .…”
Section: The Sfr and Gas-phase Metallicitymentioning
confidence: 97%
“…Furthermore, the metallicity difference can be as large as 0.2 dex, which is roughly equal to what we find here. The dominated mechanism of this finding is still under debate (Ellison et al 2008;Yabe et al 2012;Sánchez Almeida et al 2014;Wang et al 2017;Sánchez Almeida & Dalla Vecchia 2018), which is likely a combined effect of metal-poor gas accretion, metalrich gas outflow, and the metal-enrichment from current star formation activities. However, the metallicity difference between cSFGs and eSFGs vanishes at stellar mass greater than 10 10.5 M ⊙ .…”
Section: The Sfr and Gas-phase Metallicitymentioning
confidence: 97%
“…The three diagnostic parameters have long been used to indicate the recent SFHs on different timescales (e.g. Worthey & Ottaviani 1997;Balogh et al 1999;Kauffmann et al 2003;Li et al 2015;Wang et al 2017Wang et al , 2018. In SF galaxies, the Hα emission mainly comes from the recombination of gas ionized by photons from extremely massive stars (>15M ⊙ ), which is therefore expected to trace the SFHs within the lifetime of these massive stars (∼5 Myr).…”
Section: The Diagnostic Observational Parameters Of the Recent Sfhsmentioning
confidence: 99%
“…The Hα emission is a good tracer of the SFR averaged within the last 5 Myr, the EW(Hδ A ) traces the star formation within the last roughly ∼1 Gyr, and the 4000Å break is sensitive to the lightweighted stellar age within 2 Gyr (e.g. Balogh et al 1999;Kauffmann et al 2003;Li et al 2015;Wang et al 2017Wang et al , 2018. These three parameters can be directly measured from galaxy spectra, and each being measured at a single wavelength they are all, in principle, insensitive to dust attenuation, although dust effects can still enter if different components of the system suffer different extinctions (this is explored in Section 2.6 below).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we also find that the residuals for concentration index C and gravitational potential Φ are nearly zero, meaning that the local metallicity may be independent on the galaxy concentration and average gravitational potential. Recently, Wang et al (2017) have demonstrated that the local metallicity also depends on the assembly modes of galaxies. In the sense that higher Σ * (denser) regions, located in the inner regions of galaxies with an "outsidein" assembly mode, have higher metallicity and lower D n 4000 than those galaxies with an "inside-out" mode.…”
Section: 2mentioning
confidence: 99%